Religious identity and renewal in the twenty-first century: Christian and Muslim explorations - Sinn, Simone; Trice, Michael Reid (Documentation, 2015)
Preface / Martin Junge -- Introduction / Michael Reid Trice and Simone Sinn -- I. God, generosity and theodicy. The future of religious identity : a spirit of generosity / Michael Reid Trice ; Jews, God and theodicy / Anson Laytner -- II. Religious voice, dialogue and renewal. Challenges to religious identity in the twenty-first century / John Borelli ; The role of the religous voice in the twenty-first century -- a Jewish perspective / Shira Lander -- III. Memory, tradition and revelation. Scripture and revelation in the Jewish tradition / David Fox Sandmel ; The role of memory in the formation of early Christian identity / Binsar Jonathan Pakpahan ; Sacred text, revelation and authority : remembering and transmitting the word / Nelly van Doorn-Harder -- IV. Case studies : Twenty-first-century formation of community. Forming roots in the midst of rootlessness : religious identity in the Pacific Northwest / Catherine Punsalan-Manlimos ; The renaissance that never happened : considering the institutional challenges of Judaism in Germany / Paul Moses Strasko ; The changing face of religions in southern Africa / Herbert Moyo -- V. Intersection of identities. Ummah at the intersection of identities / Celene Ibrahim-Lizzio ; Who are we and what constitutes our identity / Suneel Bhanu Busi